Holy terrors Latin American women perform - Taylor, Diana 1950-; Costantino, Roselyn (Duke University Press, 2012)
Manifesto 2000 of feminine humor ; From the waist down / Shanna Lorenz -- What is Diana Raznovich laughing at? / Diana Taylor -- Strip / Griselda Gambaro -- Excerpts from E. luminata : "From her forgetfulness project" and "Dress rehearsal" / Diamela Eltit -- Diamela Eltit : performing action in dictatorial Chile / Robert Neustadt -- Excerpts from "Essential theatre" ; CASA / Denise Stoklos -- The gestural art of reclaiming Utopia : Denise Stoklos at play with the hysterical-historical / Leslie Damasceno -- Lyrics to "Corazon sangrante : "Bleeding heart" and "La tequillera" ; Monologues (selections) / Astrid Hadad --
Informationen wurden der Landingpage entnommen, da weder Titelblatt noch Impressum vorhanden sind (Duke University Press)
Keywords: Latin American drama / Translations into English / Women authors; Latin American drama / Translations into English / 20th century; Frauentheater; Schriftstellerin; Drama; Lateinamerika; Anthologie; Aufsatzsammlung